Numerical simulation of the fracture and compression response of self-healing concrete containing engineered aggregates. (February 2023) - Pan, Xiaoying; Gencturk, Bora; Alnaggar, Mohammed; Sohail, Muazzam Ghous; Kahraman, Ramazan; Al Nuaimi, Nasser; Rodrigues, Debora F.; Yildirim, Yucel
Abstract: The existing self-healing concretes that rely on capsules require modifications to one or more traditional concrete mixing, placing, and consolidating methods. Additionally, concrete mixture designs need alterations to accommodate these self-healing capsules. This paper presents the development and characterization of a novel encapsulation method for self-healing concrete. This method, using engineered aggregates (EA), features macro-capsules with a cementitious coating, a brittle container, and a healing agent. Like coarse aggregates, the EA are randomly dispersed in the concrete, and they are added just like any other admixture during the mixing process. Lattice discrete particle models (LDPM) were developed employing randomly packed coarse aggregates and EA with different volume fractions, shapes, sizes, coating thicknesses, and different coating mortars. The models were calibrated using experimental results of split tensile, four-point bending, and uniaxial compression tests. The formation and propagation of cracks in the concrete matrix and EA were observed in the LDPM models. A detailed presentation of the stresses inside the EA and the concrete matrix was obtained. Stress concentration in the EA was affected by the strength of the coating mortar and the shape of EA. Parametric studies were conducted to understand the effect of volume fraction of EA, EA coating thickness, and strength on the overall mechanical behavior of concrete. The results suggest that using coating mortar with higher strength can increase the load-carrying capacity of the concrete, especially when the coating is thicker, but reduce the crack opening in the EA when the crack occurs. The concrete's strength increases with the cavity's size inside the EA at the same EA dosage. These simulations inform the EA design and develop an understanding of the effect of EA on the load-carrying capacity of concrete.